Cardiovascular magnetic resonance in rheumatology: Current status and recommendations for use. (15th August 2016) - Mavrogeni, Sophie I.; Kitas, George D.; Dimitroulas, Theodoros; Sfikakis, Petros P.; Seo, Philip; Gabriel, Sherine; Patel, Amit R.; Gargani, Luna; Bombardieri, Stefano; Matucci-Cerinic, Marco; Lombardi, Massimo; Pepe, Alessia; et al.
Abstract: Targeted therapies in connective tissue diseases (CTDs) have led to improvements of disease-associated outcomes, but life expectancy remains lower compared to general population due to emerging co-morbidities, particularly due to excess cardiovascular risk. Cardiovascular magnetic resonance (CMR) is a noninvasive imaging technique which can provide detailed information about multiple cardiovascular pathologies without using ionizing radiation. CMR is considered the reference standard for quantitative evaluation of left and right ventricular volumes, mass and function, cardiac tissue characterization and assessment of thoracic vessels; it may also be used for the quantitative assessment of myocardial blood flow with high spatial resolution and for the evaluation of the proximal coronary arteries. These applications are of particular interest in CTDs, because of the potential of serious and variable involvement of the cardiovascular system during their course. The International Consensus Group on CMR in Rheumatology was formed in January 2012 aiming to achieve consensus among CMR and rheumatology experts in developing initial recommendations on the current state-of-the-art use of CMR in CTDs. The present report outlines the recommendations of the participating CMR and rheumatology experts with regards to: (a) indications for use of CMR in rheumatoid arthritis, the spondyloarthropathies, systemic lupus erythematosus, vasculitis of small, medium and large vessels, myositis, sarcoidosis (SRC), and scleroderma (SSc); (b) CMR protocols, terminology for reporting CMR and diagnostic CMR criteria for assessment and quantification of cardiovascular involvement in CTDs; and (c) a research agenda for the further development of this evolving field. Highlights: CMR can evaluate symptomatic CTDs with normal routine noninvasive findings. CMR can exclude myocarditis and perform stress perfusion in CTDs, unable to exercise. CMR can evaluate myocardial and/or vascular inflammation in vasculitis. CMR can evaluate CTDs with LV dysfunction, block, arrhythmia or inconclusive tests. CMR can be used in CTDs as a gatekeeper for coronary angiography.